2007
DOI: 10.1128/iai.01908-06
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Pigs To Prevent Disease in Humans: Construction and Protective Efficacy of a Salmonella enterica Serovar Typhimurium Live Negative-Marker Vaccine

Abstract: Zoonotic infections caused by Salmonella enterica serovar Typhimurium pose a constant threat to consumer health, with the pig being a particularly major source of multidrug-resistant isolates. Vaccination, as a promising approach to reduce colonization and shedding, has been scarcely used, as it interferes with current control programs relying on serology as a means of herd classification. In order to overcome this problem, we set out to develop a negative-marker vaccine allowing the differentiation of infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Vaccination may thus hamper the use of serology for Salmonella monitoring programmes. Programmes that are based on bacteriology, new diagnostic tests that do not detect vaccine-induced antibodies (Selke et al, 2007), or new vaccines that are not detected by current ELISA methods (Leyman et al, 2011) are necessary if vaccination is to become a routine part of Salmonella control.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination may thus hamper the use of serology for Salmonella monitoring programmes. Programmes that are based on bacteriology, new diagnostic tests that do not detect vaccine-induced antibodies (Selke et al, 2007), or new vaccines that are not detected by current ELISA methods (Leyman et al, 2011) are necessary if vaccination is to become a routine part of Salmonella control.…”
Section: Discussionmentioning
confidence: 99%
“…Trials have reported safety and some degree of efficacy when it has been used in experimental ST-challenge studies. These have involved vaccinating dams and/or pre-weaned piglets [18], or vaccinating weaners subsequently challenged by oral dosing [19,20] or by seeder pigs [21]. The rationale to vaccinate dams is to reduce shedding around farrowing and to provide passive immunity to offspring [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nontyphoidal salmonellosis (NTS) still has an important impact on public health in developed countries [3] and the consumption of pork is increasingly referred to as a major source of human infection [5,6]. Vaccination is one of the methods suggested to decrease the burden of S. Typhimurium at the swine farm level and to prevent dissemination of bacterial microorganisms through the pork production chain.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is usually characterized by self-limiting gastroenteritis in humans, but may occasionally cause fever and systemic infection [1,2]. Salmonellosis along with being a public health concern, is a economic problem as it also affects livestock breeding [3,4]. 26.9% of the human cases in the EU are caused by contaminated pork meat [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%